A Case Report: Aneurysmal Bone Cyst Of Proximal Femur With Subtrochanteric Femur Fracture In A Child (Journal of Pharmaceutical Negative Results, 2022)
Aneurysmal bone cysts are blood-filled lesions of the bone that are benign, expansile, aggressive, and locally damaging. They havean atypical presentation and an unknown etiology. We present the case of a 17-year-old male youngster who appeared with a historyof trauma that resulted in a pathological left femur fracture. A subtrochanteric fracture complicated a slowly forming aneurysmalbone cyst in the proximal femur. Excision of the tumor with curettage and open reduction with internal fixation with a titanium elasticnail were successful treatments, and the empty space was replaced with bone graft from the left iliac crest. The gold standard fordiagnosis is a biopsy. Bone grafting should be used in conjunction with fracture fixation to achieve bony union.